Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean - Fricke, Ronald (Zootaxa, 2018)
Two new species of stargazers in the Uranoscopus albesca species-complex of the family Uranoscopidae are described from Papua New Guinea, which shares among other characters a concave posterodorsal margin of the pectoral fin. Uranoscopus brunneus n. sp. is described from a single specimen from off southwestern New Britain, and is characterised by lower edge of preopercle with 8 spines; labial fimbriae poorly-developed; anterior nostril with a long tubiform valve, posterior nostril a slit-like pore; supracleithrum with a sharp spine at rear end and five small spines inside; dorsoposterior margin of pectoral fin concave; 62 oblique scale-rows along the sides of the body in adult; pectoral-fin membranes dark brown. Uranoscopus kishimotoi n. sp., described from a single specimen from West Sepik Province, is characterised by the lower edge of preopercle with 3 spines; no labial fimbriae; both anterior and posterior nostrils with long tubiform valves; supracleithrum with a sharp spine at rear end and one additional small spine inside; dorso-posterior margin of pectoral fin concave; 59 oblique scale-rows along the sides of the body in adult; upper pectoral-fin membranes pale, lower membranes brown. The distribution of the species in the U. albesca species-complex is discussed.